1979
DOI: 10.1017/s002185960005396x
|View full text |Cite
|
Sign up to set email alerts
|

Results from three cycles of six-course rotations on light land

Abstract: A rotation experiment comparing the effects of length, type and management of leys on three test crops in six-course rotations during three cycles is described and the results discussed.Although the yields of the test crops varied from cycle to cycle there were no clear-out trends to suggest that the yield improves or deteriorates as time goes on with these particular rotations; the full benefit of the leys was obtained in the first cycle.The yield of potatoes immediately following the leys was no greater than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1982
1982
2011
2011

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…(Karlen et al 1994;Berzsenyi et al 2000). Hanley & Ridgman (1979) found that the full benefits of the leys were obtained already during the first rotation cycle. However, other results have shown that soil fertility changes over time due to effects of crop rotation on both amount and quality of plant residues (Persson & Mattsson 1993;Drinkwater et al 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Karlen et al 1994;Berzsenyi et al 2000). Hanley & Ridgman (1979) found that the full benefits of the leys were obtained already during the first rotation cycle. However, other results have shown that soil fertility changes over time due to effects of crop rotation on both amount and quality of plant residues (Persson & Mattsson 1993;Drinkwater et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that all grassclover production was left in the field as a mulch, which probably has profound effects on soil N fertility. Grass-clover leys have been found to increase the yield potential of following cereals beyond that which can be compensated by N fertilization (Hanley & Ridgman 1979;Johnston et al 1994;Uhlen et al 1994;Eriksen 2001). Such fertility effects may be mediated through effects on soil quality, diseases, etc.…”
Section: Discussionmentioning
confidence: 99%
“…There are few published studies of yield over more than one rotational cycle in conventional systems, e.g. Hanley and Ridgman (1979), however, it is difficult to use those to inform organic farming as the N effects of the ley are likely to have been masked by the use of soluble nitrogen fertilisers on the arable crops in the rotation.…”
Section: Differences Between Rotationsmentioning
confidence: 99%